Role of Cyber Twin Mobile Networks in Digital Communication - Asokan, R. (IRO Journal on Sustainable Wireless Systems, 2023)
Due to the unprecedented increase in the utilization of Internet of Things (IoT) technology, there is a huge increase in network/internet traffic due to which the existing network architectures are facing number of challenges in terms of reliability, availability, scalability, portability and expandability. In order to deal with the challenges, the cyber-twin technology has been recently proposed to assist in establishing a strong communication network in terms of digital asset management, network data maintenance etc. Recently, cyber-twin has become a well-established environment for real-world applications ranging from manufacturing, healthcare to smart city applications. The proposed study reviews the concept of cyber-twin mobile networks along with a representation and efficient utilization of cyber-twin networks and its impact in the digital world. Further, different state-of-the-art cyber-twin architectures are compared to show how these architectures outperform the traditional peer-to-peer networks in order to make the futuristic networks safer, secured, adaptable, portable and reliable.Due to the unprecedented increase in the utilization of Internet of Things (IoT) technology, there is a huge increase in network/internet traffic due to which the existing network architectures are facing number of challenges in terms of reliability, availability, scalability, portability and expandability. In order to deal with the challenges, the cyber-twin technology has been recently proposed to assist in establishing a strong communication network in terms of digital asset management, network data maintenance etc. Recently, cyber-twin has become a well-established environment for real-world applications ranging from manufacturing, healthcare to smart city applications. The proposed study reviews the concept of cyber-twin mobile networks along with a representation and efficient utilization of cyber-twin networks and its impact in the digital world. Further, different state-of-the-art cyber-twin architectures are compared to show how these architectures outperform the traditional peer-to-peer networks in order to make the futuristic networks safer, secured, adaptable, portable and reliable.